Morbidity experienced by women before and after operative vaginal delivery: prospective cohort study nested within a two‐centre randomised controlled trial of restrictive versus routine use of episiotomy. Issue 8 (6th March 2013) - Macleod, M; Goyder, K; Howarth, L; Bahl, R; Strachan, B; Murphy, DJ
<x xml:space="preserve">Abstract</x> Objective To explore: (1) the antenatal and postnatal morbidity experienced by women in relation to operative vaginal delivery (OVD); and (2) the impact of restrictive versus routine use of episiotomy. Design Longitudinal prospective cohort study embedded within a two‐centre randomised controlled trial (RCT). Setting Two UK tertiary‐level maternity units. Population Antenatally recruited participants of an RCT of restrictive versus routine use of episiotomy at OVD. Methods A self‐completing questionnaire was administered antenatally, before hospital discharge, at 6 weeks and at 1 year postpartum. Main outcome measures Urinary and anal incontinence, dyspareunia, perineal pain and psychological morbidity. Results Longitudinal data have revealed that morbidities historically associated with OVD were often as prevalent, if not more prevalent, in the third trimester of pregnancy than postpartum. Restrictive episiotomy use was associated with: a higher incidence of perineal pain in the immediate postpartum period (98.9% restrictive versus 87.8% routine, RR 1.10, 95% CI 1.01–1.21); greater psychological morbidity in the immediate postpartum period (mean scores on the Edinburgh Postnatal Depression Scale, Edinburgh Postnatal Depression Score (EPDS) 6.7 restrictive versus 5.1 routine; P = 0.01 ); and more stress urinary incontinence at 6 weeks postpartum (42.2% restrictive versus 27.2% routine, RR 1.55, 95% CI 1.00–2.40); however, this had resolved by 1 year. No other differences were found between the groups at 6 weeks and 1 year postpartum. Conclusions Morbidities previously attributed to OVD may in fact be present antenatally, to a greater or similar degree. A restrictive approach to the use of episiotomy at OVD may increase rates of urinary morbidity, in particular stress incontinence and perineal pain, in the immediate postpartum period.